Building partnerships in social work education: Towards achieving collaborative advantage for employers and universities. (January 2014) - Wilson, George
Summary: Better partnership working between employers and academic institutions has recently been identified as one of the key developments needed to improve social work education and practice in the UK (Social Work Reform Board, 2010). However, the praxis of collaborative working in social work education remains under-researched and it is unclear what factors are significant in promoting effective partnership. This article contributes to this debate by reporting research that examined the experience of social work academics working with employers to deliver qualifying level social work education in Northern Ireland. Findings: This analysis explores key factors in the dynamics of the collaborative process and identifies both congruence and discord in academic and employer perspectives. The findings highlight the collaborative advantage accruing from partnership working, which include the benefits of a centrally coordinated system for the management and delivery of practice learning. However, the results also indicate that engaging in partnership working is a complex process that can create conflict and tensions, and that it is important to ground collaborations in realistic expectations of what can be achieved. Application: This article identifies opportunities for achieving collaborative advantage and the challenges. It identifies lessons learned about the value of partnership working in social work education and ways to increase its efficacy.